The Green Hotel Image Affecting Hotel Selection in Chiang Rai - Pingyot, Natthakit; Yodsuwan, Chachaya (Journal of Management Science Chiangrai Rajabhat University, 2024)
The purpose of this research was to study green hotel image and green hotel framework towards the hotel selection in Chiang Rai. The study was a quantitative research. Data was collected by a questionnaire from 400 Thai green tourists, randomly selected with convenient sampling. The quality of the tool was tested by experts and the values of the Index of Item Objective Congruence was 1.00. A pilot test study reported a Cronbach’s alpha coefficient of 0.928. The data were analyzed with the statistics of descriptive and inference, including multiple regression analysis. The results showed that 1) Factors of the green hotel image consist of brand image, product or service image and organizational image have an influence on hotel selection in Chiang Rai with statistical significant. And 2) Factors of the green hotel framework consist of the environmental impact reduction policy, the collaboration with local communities policy, the resource efficiency enhancement policy and the formulation of environmentally friendly service policy have an influence on hotel selection in Chiang Rai with statistical significant.